Socio-economic Characteristics of Lac Growers in Kanker District of Chhattisgarh - Pal, Govind (Indian Forester, 2011)
The study pertains to data collected from randomly selected 100 lac growers in Kanker district of Chhattisgarh for the year 2008- 09. The study resulted that 39 per cent lac growers were medium farmers followed by small (25 per cent), marginal (18 per cent), semimedium (16 per cent) and large (2 per cent). The majority of lac growers had education up to primary level. Average family size was 5.9. Share of income from lac was 23.5 per cent in total average annual income of lac growers. Share of farm and off-farm income at growers level was 58:42. About 58 per cent lac growers had palas (Butea monosperma), 17 per cent had ber (Zizyphus mauritiana), 87 per cent had kusum (Schleichera oleosa) and 12 per cent had other host trees available for lac cultivation in the study area. Lac host utilization percentage was low due to some constraints faced by the lac growers. The host utilization percentage was maximum for palas (58.65 per cent) followed by kusum (39.76 per cent), ber (32.61 per cent) and other host (21.24 per cent). About 51.0 per cent lac growers produced lac with average production of 60.44 kg., 23.0 per cent had average production of 161.22 kg., 11.0 per cent had 234.44 kg. and 15.0 per cent had 418.08 kg. annually. Outcome of the study may be helpful in strengthening the socio-economic condition of lac growers in Chhattisgarh.